2012
DOI: 10.3354/meps09712
|View full text |Cite
|
Sign up to set email alerts
|

Marine mammal response to interannual variability in Monterey Bay, California

Abstract: The coastal upwelling ecosystem near Monterey Bay, California, is a productive yet variable ecosystem and an important foraging area for many mobile apex predators, such as marine mammals. Long-term studies are necessary to better understand how wide-ranging predators respond to temporal environmental variability; however, few of these studies exist. We conducted monthly shipboard line-transect surveys in Monterey Bay from 1997 to 2007. We identified 22 species of marine mammals, and calculated monthly and ann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 49 publications
1
10
0
Order By: Relevance
“…Cetacean species diversity in the study region (minimum 15) was comparable with diversity in other productive areas worldwide, including the northern California Current (22 species; Burrows et al ), northern Gulf of Mexico (13 species; Davis et al ), the Eastern Tropical Pacific (30 species; Ballance et al ), the Mozambique Channel (17 species; Kiszka et al ), and off the Canary Islands (16 species; Carrillo et al ). The upwelling there is considered Australia's most intense and productive (Butler et al ), and probably aggregates cetacean prey species to a degree not found around most of the Australian continent.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Cetacean species diversity in the study region (minimum 15) was comparable with diversity in other productive areas worldwide, including the northern California Current (22 species; Burrows et al ), northern Gulf of Mexico (13 species; Davis et al ), the Eastern Tropical Pacific (30 species; Ballance et al ), the Mozambique Channel (17 species; Kiszka et al ), and off the Canary Islands (16 species; Carrillo et al ). The upwelling there is considered Australia's most intense and productive (Butler et al ), and probably aggregates cetacean prey species to a degree not found around most of the Australian continent.…”
Section: Discussionsupporting
confidence: 57%
“…Managing marine biodiversity requires an understanding of the species assemblages that inhabit marine systems (Zacharias and Gregr ). Such systems include upwelling regions, which typically support high densities of marine fauna (Mann and Lazier ), and high cetacean diversity (e.g., Ballance and Pitman , Tynan et al , Burrows et al ).…”
mentioning
confidence: 99%
“…Monthly whale densities (number of individuals per km 2 ) were calculated from line transect data using the Multiple Covariate Distance Sampling (MCDS) analysis engine in Distance software (Buckland, Anderson, Burnham, & Laake, ; Thomas et al., ). Detailed description of density analysis is presented in Burrows, Harvey, Newton, Croll, and Benson ().…”
Section: Methodsmentioning
confidence: 99%
“…The distribution and abundance of baleen whales on the eastern Bering Sea shelf also changed between 1999 and 2004 as a result of corresponding temperature increases over this period [46]. Littaye et al [47] showed that fin whales adapted their movements and group size to food availability which was driven by the environmental conditions in the preceding months, while off Monterey Bay, California, 12 commonly sighted species of marine mammals redistributed annually depending on the prevailing environmental conditions [48]. In El Niño years, when basin-wide decreases in primary production were documented, marine mammals would move from offshore to nearshore areas because of the relatively greater productivity, while during localised events marine mammals, including blue whales, redistributed to the areas influenced by the anomaly [48].…”
Section: Figurementioning
confidence: 99%